All vår början bliver svår... På väg mot en färöisk-tysk ordbok - Timmermann, Ulf (Nordiske Studier i Leksikografi, 2003)
The task of writing dictionaries in the Faroes is mostly one man’s work. The author deals with conditions, needs, concept, shape and some special problems concerning his work on a Faroese-German dictionary, which is mainly intended for upper secondary-school pupils. In order to write a useful dictionary during the 21/2 years he has at his disposition, he follows a frequency list of Faroese words which enables him to treat a lot of idioms that are connected with the most frequent words.